Management and Burden of Hidradenitis Suppurativa: An Italian Hybrid Real-World Study - Anna Balato; Marina Venturini; Massimiliano Scalvenzi; Caterina Foti; Giovanni Maifredi; Simona Serao Creazzola; Stefania Antonacci; Arianna Tonelli; Diletta Valsecchi; Donatella Vassellatti; Riccardo Cipelli; Alessandra Ori; et al. (Dermatology and Therapy)
Abstract Introduction Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease that severely impacts quality of life and carries a substantial economic burden. Methods This multicenter observational study generated real-world evidence on HS in Italy, focusing on clinical profiles, management, and costs. Data were collected from 50 adults at four specialized centers, combining primary data with retrospective administrative data. Results Patients with moderate-to-severe disease had longer diagnostic delays (median 1.8 versus 0.7 years), lower symptom control (40.7% versus 95.2%), and worse quality of life (Dermatology Life Quality Index: 11.8 versus 8.0) than those with mild disease. Furthermore, HS was associated with higher costs in moderate-to-severe cases, including greater direct (€2214 versus €873) and indirect expenses (€2435 versus €262). Conclusions The findings highlight the social and economic burden of HS and emphasize the need for increased healthcare awareness for earlier diagnosis and better management.